Intravascular Molecular Imaging: Near-Infrared Fluorescence as a New Frontier - Khraishah, Haitham; Jaffer, Farouc A. (Frontiers in Cardiovascular Medicine, 2020)
Despite exciting advances in structural intravascular imaging (intravascular ultrasound (IVUS) and optical coherence tomography (OCT)) that have enabled partial assessment of atheroma burden and high-risk features associated with acute coronary syndromes, structural-based imaging modalities alone do not comprehensively phenotype the complex pathobiology of atherosclerosis. Near-infrared fluorescence (NIRF) is an emerging molecular intravascular imaging modality that allows for in vivo visualization of pathobiological and cellular processes at atheroma plaque level, including inflammation, oxidative stress, and abnormal endothelial permeability. Established intravascular NIRF imaging targets include macrophages, cathepsin protease activity, oxidized low-density lipoprotein and abnormal endothelial permeability. Structural and molecular intravascular imaging provide complementary information about plaque microstructure and biology. For this reason, integrated hybrid catheters that combine NIRF-IVUS or NIRF-OCT have been developed to allow co-registration of morphological and molecular processes with a single pullback, as performed for standalone IVUS or OCT. NIRF imaging is approaching application in clinical practice. This will be accelerated by the use of FDA-approved indocyanine green (ICG), which illuminates lipid- and macrophage-rich zones of permeable atheroma. The ability to comprehensively phenotype coronary pathobiology in patients will enable a deeper understanding of plaque pathobiology, improve local and patient-based risk prediction, and usher in a new era of personalized therapy.